(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of Aflatoxin B1 contamination in corn, rice, peanut and sesame samples in Hanoi from 2022 to 2023. Research objects and methods: Cross-sectional descriptive study with analysis. The research subjects are rice, corn, peanuts and sesame samples in Dong Da district and Quoc Oai district, Hanoi, collected from January 2022 to March 2023. Results: The average concentration of AFB1 in 180 research samples was 2.86 ± 5.08 μg/kg, the highest concentration was 29.1 μg/kg, the average AFB1 content in peanuts and sesame samples was the largest (4.43 μg/kg), then corn (3.74 μg/kg) and the lowest was in rice (1.25 μg/kg). There were 82 samples contaminated with AFB1 (45.6%), 34 samples (31.7%) exceeded the maximum allowable value. Of these, the rate of peanuts and sesame samples contaminated with AFB1 is highest (33/60, accounting for 55%), followed by corn and corn products (21/40, accounting for 52.5%), and the lowest rate was in rice and processed products from rice (28/80 accounts for 35%). The percentage of samples exceeding the maximum allowable value in samples collected in Dong Da district is 26.7%, higher than this percentage in samples collected in Quoc Oai district (11.1%). Conclusion: The study showed the need to establish management guidelines relates to the prevalence of AFB1 mycotoxins in Hanoi’s food and to regularly monitor highly consumed foods, especially especially rice and cereals.